Răspuns :
x+y=123
y⇒ I..........I 83
x ⇒ I..........I.........I 49
y=(123+49+83):3=85
y=85-49=36
x=85x2-83=170-83=87
Proba ⇒87+36=123
y⇒ I..........I 83
x ⇒ I..........I.........I 49
y=(123+49+83):3=85
y=85-49=36
x=85x2-83=170-83=87
Proba ⇒87+36=123
x + y =123 si
x+83 = 2*(y+49) => x+83=2y+98 => x-2y = 15
din cele doua ecuatii obtinem:
x+y = 123 -
x-2y = 15
--------------
y-(-2y) = 108 => 3y=108 ... y = 108:3=36
deci: y=36 si x=123 - 36= 87
x+83 = 2*(y+49) => x+83=2y+98 => x-2y = 15
din cele doua ecuatii obtinem:
x+y = 123 -
x-2y = 15
--------------
y-(-2y) = 108 => 3y=108 ... y = 108:3=36
deci: y=36 si x=123 - 36= 87